The role of AGG interruptions in fragile X repeat expansions: a twenty-year perspective - Latham, Gary J.; Coppinger, Justine; Hadd, Andrew G.; Nolin, Sarah L. (Frontiers in Genetics, 2014)
In 1994, it was suggested that AGG interruptions affect the stability of the fragile X triplet repeat. Until recently, however, this hypothesis was not explored on a large scale due primarily to the technical difficulty of determining AGG interruption patterns of the two alleles in females. The recent development of a PCR technology that overcomes this difficulty and accurately identifies the number and position of AGGs has led to several studies that examine their influence on repeat stability. Here, we present a historical perspective of relevant studies published during the last 20 years on AGG interruptions and examine those recent publications that have refined risk estimates for repeat instability and full-mutation expansions.